Rapid scientific update response to public health professions during Phase I of COVID-19 pandemic. (30th September 2020) - Caminada, S; Angelozzi, A; Barbaro, A; Brambilla, G; Carusi, D; De Castro, P; Gentili, D; Mistretta, A; Mochi, P; Rosi, A
Abstract: Issue: Preparedness can be considered the Achilles heel in Western Coutries to adequately fight Sars-CoV-2 pandemy. The Istituto Superiore di Sanità (ISS) has been challenged to give rapid technical and scientific advices to the State and Regions on a huge variety of Sars-CoV-2 aspects related to public health. Description of the problem: Rapid and timely accumulation of knowledge and empirical evidence is critical for policymakers and emergency managers to maximally inform their decisions through scientific evidence and to better guide and mobilise the expertise of academics and general practitioners towards effective solutions. Results: An ad hoc "Scientific Literature working group" at ISS in the period 23/03 - 31/05 screened a total of 4, 568 pre-prints and 15, 590 peer reviewed papers extracted from PubMed, arXiv.org, medRxiv and bioRxiv, which gave rise to the following deliverables: a) a daily pre-prints alert selection delivered to ISS President for the routine national Scientific Technical Committee meetings on Sars-CoV-2 chaired by Italian Civil Protection (still ongoing), and, b) a weekly open access issue of Covid Contents publications (8 volumes, https://www.iss.it/en/covid-contents ), as summary of most interesting peer-reviewed papers for public health professions. Lessons: The needed cross-cutting approach is leading to: interdisciplinarity enhancement within the ISS; coverage of broad expertise areas and interest of health care providers; cross-linkage between the different aspects/disciplines involved in this pandemic and share of experiences. Key messages: Committed Institutions have the responsibility to support practitioners and decision makers to understand relevant aspects of medical, physical, occupational and public safety, in case of emergency. The Silos culture has to be overcome. There is nothing more powerful in any Institution than having all researchers rowing fiercely in the same direction.